Morphology of echinococcal liver lesions during treatment with high-intensity focused ultrasound - Galina Fedotovskikh; Galiya Shaymardanova; Nurlan Zhampeissov (National Scientific Medical Center, 2022)
Aim: The purpose of morphological studies was to study pathogenetic mechanisms of the therapeutic effect of HIFU ablation on hepatic echinococcosis. Material and methods: Ablation of echinococcal cysts and alveococcal liver lesions no larger than 5 cm in size with high-intensity focused ultrasound was performed on JC Focused Ultrasound Therapeutic System (China). Biopsy material of hepatic echinococcal masses in 37 patients after HIFU-ablation were taken for morphological light-optical and electron microscopic studies. Results: Protoscolexes lost their superficial syncytial layer, the parenchyma looked vacuolized, the disembodied heads with suckers and hooks were fragmented and separated from the body. Small vacuolization of hyaloplasm, homogenization of membranes and mitochondrial matrix, blurring of organelle contours in parenchymatous protoscolex cells were observed. Laminar shells of brood capsules and larvocysts of echinococcus were homogenized and ruptured, germinative cells were sloughed off. The laminar and germinal sheaths of the alveolar vesicles were irregularly thickened, unfolded, ruptured, and surrounded by necrotized liver cells and structureless masses. Destructively altered stem cells and calcareous calcium corpuscles of the laryngeal membrane were observed electron microscopically. Conclusion: Morphological data revealed destructive effect of HIFU ablation on mature and germinative forms of hydatid and alveolar echinococcus of the liver, as well as the safety of the selected optimal HIFU power on the surrounding hepatic tissue, which explains the absence of recurrence and confirms high effectiveness of HIFU ablation as a minimally invasive method of treatment of echinococcal growths of certain acceptable sizes.